PROSES BERPIKIR KREATIF SISWA SMP DALAM PENGAJUAN MASALAH MATEMATIKADITINJAU DARI GAYA KOGNITIF SISWA (Studi Kasus pada Siswa Kelas VIII-H SMP Negeri 1 Sukoharjo Tahun Pelajaran 2012/2013) - Komarudin, Komarudin; Sujadi, Imam; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2014)
Abstract: This study aimed to describe the process of creative thinking of students of SMP Negeri 1 Sukoharjo who have the type of cognitive style field-independent (FI) and field-dependent (FD) in the mathematics problems posing on Wallas steps, namely preparation, incubation, illumination, and verification. This research was a case study. The data collection techniques conducted by using think aloud method. The results showed that the process of creative thinking on: (1) the FI students, namely (a) the preparation, students read silently APP (assignment problem posing), observe the instructions and image information carefully, and students can know the things that are known on first reading of APP; (b) incubation, the students tend to be silent for a moment, it is as a start in developing a mathematical problem; (c) illumination, the students determine the attributes and the things that will be proposed to the problem, students verbalize the problem as he bowed his head, after that, the students write the problem in the worksheet and if something goes wrong on the issues raised, the students tend to immediately fix the problem; (d) verification, the students correct mathematical issues raised, explain the troubleshooting procedures and resolving the issues raised at worksheet, students corrected back problems and the settlement has been made; (2) Students FD, namely (a) the preparation, students read silently APP, observe the instructions and image information on the APP, to find the information and the things that are known, students need to read back the APP; (b) incubation, the students tend to be silent for a moment, this is the first step in preparing mathematics problems, in this step, students were less calm and worried while playing both hands; (c) illumination, the students determine the attributes and things to issues raised by several silent, students write the problem in the worksheet and if something goes wrong on the issues raised, the students tend to replace the problem; (d) verification, the student explains the troubleshooting procedures and resolves the issues raised at worksheet, students corrected the solved problem and solution.Keywords: creative thinking, problems posing, and cognitive style.